The origins and use of the potter's wheel in ancient Egypt - Doherty, S. K. (Archaeopress Egyptology, 2015)
The invention of the wheel is often highlighted as one of humankinds' most significant inventions. Wheels do not exist in nature, and so can be viewed entirely as a human-inspired invention. Machinery too, was relatively rare in the ancient world. The potter's wheel is arguably the most significant machine introduced into Egypt, second only perhaps to the drill, the loom and the bellows for smelting metal. This volume examines this topic.